Analysis Of Rainfall Characteristics In Balikpapan City Based On Data From Balikpapan Meteorological Station - Riza Hudayarizka; Ismi Khairunnissa Ariani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
This study objected to finding the best-fit probability distribution method using four distributions: Normal Distribution, Gumbel Distribution, Log Normal Distribution, and Log Pearson Type III Distribution. According to the score of the goodness-of-fit test, Log Pearson Type III was selected as the best-fit probability distribution. Design rainfall and rainfall intensity were also calculated for the return period of 2 years, 5 years, 10 years, 15 years, and 25 years. In relation to the rainfall intensity, the IDF curve was created. The IDF curve shows higher intensity in the first 5 hours of rainfall, and then the trend decreases gradually. Moreover, it shows that the higher the return period, the higher the rainfall intensity. The movement of curves is essential for designing drainage, flood intensity, and planting period.